PENDIDIKAN PEMBERDAYAAN MASYARAKAT DENGAN MENANAMKAN PENGETAHUAN ISLAMI DAN EKONOMI SYARIAH DI DUSUN I DESA CIBEBER II - Dewi, Intan Kusuma; Rahman, Irfan Hifdzur; Mahardika, Afftah Rizki; Ibrahim, Anwar; Anwar, Dera Azkia; Rahmawati, Fatihah Rizki; Utami, Gusti Faoziah Tri; Hendra, Mohamad; Rizqi, Muchammad; Salsabila, Shafa Tania; Chodijah, Siti; Amri, Andi (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Community empowerment is an important form of program in increasing community participation. The implementation of empowerment will be more effective and efficient with the role of the government, community, academics, and other supporting parties. Especially the role of universities in community empowerment with KKN programs is also applied to the University of Muhammadiyah Prof. DR. HAMKA with the title KKS.Based on the level of crisis that occurs in the community, the theme of Community Empowerment Education by Instilling Islamic Knowledge and Sharia Economics is determined. The PSC program was carried out in Hamlet I of Cibeber II Village, Bogor Regency, West Java. There are main programs and assistance programs in this PSC activity.The main work program consists of the field of educational empowerment and the field of Islamic economics. The assistance work program consists of organizing village information posts and local RT\/RWs.The implementation of the main work program and assistance received a positive response and there was even active participation from the Village Head, Village Staff, Head of RT, Head of RW, children in Cibeber II Village and the people of Cibeber II Village so that everything went smoothly and there was even a special request to continue the program from the KKS group.